10.1016/s0197-2510(06)70444-2 (CrossRef Listing of Deleted DOIs, 2000)
Agranulocytosis is a rare but serious side effect of antithyroid drugs (ATDs), defined by an absolute neutrophil count (ANC) below 500/μL; some patients develop a more severe form with ANC below 100/μL. We retrospectively compared the clinical, biochemical, and HLA-B allele profiles between the two presentations in 24 cases of ATD-induced agranulocytosis. Based on nadir ANC, 15 participants with ANC < 100/μL formed the severe group and 9 with ANC 100-500/μL comprised the typical group. The severe group had a significantly longer neutrophil recovery time (5 [5-7] vs. 3 [2.5-3.5] days; P = 0.003), higher median levels of total bilirubin (21.4 [13.3-30.4] vs. 7.1 [6.2-18.3] μmol/L; P = 0.003) and indirect bilirubin (9.9 [7.6-16.7] vs. 6.1 [3.6-9.8] μmol/L; P = 0.018), and fewer asymptomatic patients at presentation (0/15 vs. 5/9, P = 0.003). HLA typing confirmed that HLA-B*38:02 was associated with severe ATD-induced agranulocytosis (OR = 48.6; 95% CI = 2.3-1020.7; P = 5.9 × 10 -4 ). Sensitivity analysis excluding the 2 PTU-treated patients confirmed a robust and significant association (OR = 38.3; 95% CI = 1.8-820.2; P = 0.0039). No significant differences were observed in age, sex, drug type or dosage, or other biochemical parameters at agranulocytosis onset. Severe agranulocytosis accounted for 62.5% (15/24) of cases, highlighting it as a common clinical phenotype of ATD-induced agranulocytosis. HLA-B*38:02 is associated with susceptibility to ATD-induced severe agranulocytosis, an association predominantly driven by methimazole exposure.